Melioidosis masquerading as metastatic lung disease: A diagnostic challenge from coastal Karnataka, India (Indian Journal of Case Reports, 2026)
Melioidosis, caused by Burkholderia pseudomallei, is an emerging infectious disease in India that can closely mimic tuberculosis or malignancy, leading to diagnostic delays and mismanagement. A 54-year-old diabetic farmer from coastal Karnataka presented with fever, dry cough, anorexia, and weight loss. Imaging revealed multiple bilateral pulmonary nodules with intense fluorodeoxyglucose uptake on positron emission tomography-computed tomography (CT), suggestive of metastatic malignancy. CT-guided lung biopsy showed suppurative granulomatous inflammation, and both blood and tissue cultures confirmed B. pseudomallei. The patient received intravenous meropenem for 3 weeks followed by oral trimethoprim-sulfamethoxazole for 12 weeks, resulting in complete clinical recovery and radiological resolution. This case highlights the importance of considering melioidosis as a differential diagnosis for metastatic-appearing lung lesions in endemic regions, particularly among diabetics with soil exposure. Early microbiologic confirmation is crucial to avoid unnecessary oncologic evaluation and ensure effective antimicrobial therapy.